2008
DOI: 10.1007/s10792-008-9220-8
|View full text |Cite
|
Sign up to set email alerts
|

Ocular involvement in nasal natural killer T-cell lymphoma

Abstract: Purpose-To describe the clinical, morphologic, and immunohistochemical features of a case of paranasal natural killer/T-cell lymphoma (NKTL) with ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Like other non-Hodgkin lymphomas, it can masquerade as an intraocular inflammatory or infectious process [3], which can lead to delayed diagnosis and vision loss. The prognosis for ENKTCL is substantially worse than that of other T-cell or B-cell lymphomas [4], especially if patients present late or if there is orbital or ocular adnexal involvement [2, 5]. Early diagnosis is thus of utmost importance, but can prove quite challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other non-Hodgkin lymphomas, it can masquerade as an intraocular inflammatory or infectious process [3], which can lead to delayed diagnosis and vision loss. The prognosis for ENKTCL is substantially worse than that of other T-cell or B-cell lymphomas [4], especially if patients present late or if there is orbital or ocular adnexal involvement [2, 5]. Early diagnosis is thus of utmost importance, but can prove quite challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented orbital/ocular adnexal involvement of ENKTCL, both as a primary [5-10] and secondary [4, 10-13] manifestation of the disease. Intraocular involvement is quite rare with only a small number of published cases [4, 14-16]. To our knowledge, we are the first to report a case of ENKTCL metastatic to the space beneath the retinal pigment epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (9,10) did report a case of histologically confirmed nasal NKTL with intraocular involvement, as well as Yoo et al, (11) . In a large series of 24 cases with primary nasal and paranasal sinus NKTL, six patients suffered from vision threatening complications of uveitis/ vitritis and orbital involvement, including one with rhegmatogenous retinal detachment and one with macular hole (12) .…”
mentioning
confidence: 96%
“…T-cell IOL in the past 19,22,25 and two SRD cases were recently described on T-cell IOL. 29,30 A low rate of SRD was previously reported in B-cell lymphoma (10-28%).…”
Section: Discussionmentioning
confidence: 94%